PENGARUH 7A PARIWISATA TERHADAP MINAT BERKUNJUNG KEMBALI WISATAWAN DI MONUMEN PANCASILA SAKTI - William Suryanto; Dewanta Facrureza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of the 7A tourism components on tourists’ revisit intention at Monumen Pancasila Sakti. The background of this study is based on the importance of developing historical tourism, improving public facilities, and addressing the decline in tourist visits from 2024 to 2025. This study employed a quantitative approach, with the independent variables consisting of attraction, amenities, ancillary services, activities, accessibility, available packages, and awareness, while the dependent variable was revisit intention. Data were collected through questionnaires distributed to 100 respondents who had visited Monumen Pancasila Sakti. The data were analyzed using SPSS through validity testing, reliability testing, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that, partially, the dimensions of attraction, ancillary services, accessibility, available packages, and awareness have a positive and significant influence on revisit intention. Meanwhile, amenities and activities do not have a significant influence. Simultaneously, the 7A tourism components have a significant influence on revisit intention, as indicated by an F-count value of 8.949 > F-table value of 2.111 and a significance value of 0.000 < 0.05. The R Square value of 0.405 indicates that the 7A tourism components explain 40.5% of revisit intention, while the remaining 59.5% is influenced by other factors outside this study. This study recommends that the management improve the quality of facilities and develop innovations related to tourism components that are still considered inadequate, so that the visitor experience becomes more attractive and memorable.